Midiendo la motivación auto-determinada hacia la educación física en la escolaridad obligatoria - Rubén Navarro-Patón; Joaquín Lago-Ballesteros; Víctor Arufe-Giráldez (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
This research aim was to determine what happens to motivation during compulsory schooling. 743 students from Primary (n = 311) and Secondary School (n = 432) participated: 333 boys and 420 girls; Maged = 12.99, SD = 2.07. Statistically significant differences were found in the educational stage factor in Intrinsic Motivation (IM) (p < .001), Identified Regulation (IdR) (p < .001), Introyected Regulation (InR) (p = .004); In age factor in IM (p < .001), IdR (p < .001); External Regulation (ER) (p = .005) and Demotivacion (Dem) (p < .001). In gender factor in IM (p = .005) and IdR (p = .007). The evidences found showed a decrease of MI in the passage from primary to secondary, as these variables are higher in boys than in girls. The opposite occurs with the RE and the Dem. Based on these results, we must reflect on the teaching practice and methodology used at both educational stages, because IM should prevail towards an activity if we want to promote adherence to physical activity and sport.